A comparison of projected and actual energy performance of buildings after thermal retrofit measures. (September 2014) - Housez, Pierre Pascal; Pont, Ulrich; Mahdavi, Ardeshir
This article addresses the discrepancies between projected and actual energy performance of thermally retrofitted buildings. Toward this end, we use detailed data and observations pertaining to seven residential buildings in Austria that were thermally retrofitted recently. These include five multifamily residences in Vorarlberg, the upper level of a duplex house in Lower-Austria, and a residential complex for the elderly in Styria. During the heating season 2009–2010 (1st October–30th April), indoor temperature and relative humidity levels were measured and logged in these buildings. For each building, the actual energy use during this period was derived based on bills for gas and electrical power. Additionally, we obtained and examined existing energy calculations (energy certificates) for these buildings. In six cases out of seven, we found a large discrepancy between projected and actual space heating demand. To explore possible reasons for this discrepancy, we generated for each of the buildings an energy certificate and performed detailed thermal simulations. Thereby, we took the main input parameters for energy calculations into consideration (air change rate, indoor air temperature, outside air temperature, and internal gains). If we use standard (default) values as suggested by Austrian standards for these parameters, the above-mentioned discrepancy cannot be explained. Measurements in the buildings, as well as interviews with the building's inhabitants implied that standard-based input data assumptions were not reliable. A subsequent multi-factor study suggested that specifically the assumptions regarding air change rates might be responsible for the large deviations of the calculated values from the actual heating demand.